Дослідження методів тестування та мокування програмного забезпечення на платформі .net - Богун, В. М. (ХНУРЕ, 2024)
This work is devoted to the research of methods of creating mechanisms of testing and mocking in the context of software development on the .NET platform. It includes an analysis of the most common unit testing frameworks – NUnit, xUnit, and MSTest – focusing on their key features, attributes, and usage characteristics. The purpose of the work is to identify the optimal testing tools according to the specific conditions of the project and the environment, as well as to analyze the effectiveness of frameworks for the most productive code mocking. The main focus is on the comparative analysis of frameworks in order to find a comprehensive and effective method for improving the quality and reliability of software products.
Keywords: платформа .NET; тестові замінники; мок-об'єкти; техніки тестування